Cover blown! - Montijo, Rhode; Reynolds, Luke, 1980- (Montijo, Rhode. Gumazing gum girl!, 2019)
When Gabby and her family visit her uncle in Cobel, Mexico, she learns about her Aztec roots, and faces students from the wrestling school of her uncle's rival.